Pembangunan Permainan Video Action-Shooter 2 Dimensi Berbasis Desktop Menggunakan Game Maker Studio 1.4 - Bima Dirgantara, Harya; Windriyani, Paramaresthi (Institut Teknologi dan Bisnis Kalbis, 2020)
This study aims to build a 2-dimensional action-shooter video game using Game MakerStudio. This video game will have two types of gameplay, namely by shooting enemies and capturingenemies. The video game will be built using the Game Development Life Cycle (GDLC) process model,which consists of stages: initiation, pre-production, production, testing, beta, and release. The result ofthis research is that the desktop-based 2-dimensional beta version of the video game prototype can runaccording to its function.